KERJASAMA BISNIS KECIL DENGAN JARINGAN RITEL, DALAM MENINGKATKAN DAN MEMPERLUAS DISTRIBUSI INDUSTRI PRODUK TAS DI TANGGULANGIN SIDOARJO - Farid, M. Miftach; Maulana, Dicky Fajar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
In the era of this free market to improve the performance of small business actors in developing their business needed a real strength and partnership between small business actors as the party that produces goods with the ritail network with the goal of creating a mutual cooperation. The positive impact that can be felt with this partnership program is to make unhealthy competition between them in the long term. Because modern mini market is a container that directly related to the end consumer in selling various kinds of goods needs and other supporting goods. While small business actors also require market segments to sell all forms of goods in the production. This collaboration ultimately creates a mutually beneficial condition between small business actors and mini markets that serve to sell or ritail ing from small business products into modern ritail. This is a model that must be turned on to increase synergy between producers or small business actors with modern ritail both in rural and urban environments.